Venoarterial extracorporeal membrane oxygenation as bridge to effective treatment in a 19-year-old woman with acute adrenal crisis: a case report. Issue 2 (20th February 2021) - Lüsebrink, Enzo; Krieg, Kathrin; Massberg, Steffen; Orban, Martin
Abstract: Background: Adrenal crisis is an acute life-threatening exacerbation of the Addison's disease or primary adrenal insufficiency (PAI) and is associated with a high mortality rate. It can be the first manifestation of adrenal insufficiency and is caused by a critical lack of glucocorticoids. Case summary: Here, we report the case of a 19-year-old woman presenting to the emergency room with unspecific symptoms, i.e. lethargy, fatigue, arthralgia, dyspnoea, and hypotension. The patient's examination showed major pericardial effusion resulting in cardiac tamponade requiring immediate pericardiocentesis. In the further course, acute right heart failure and progressive cardiogenic shock occurred. Due to recurrent bradycardia and finally asystole, the patient had to be resuscitated for 15 min in total until return of spontaneous circulation. However, non-invasive haemodynamic stabilization of the patient was not successful. Hence, venoarterial extracorporeal membrane oxygenation (VA-ECMO) was used as salvage intervention to provide temporary circulatory support. We diagnosed an Addison crisis as first manifestation of her previously unknown Addison's disease. An appropriate substitution therapy with hydrocortisone and fludrocortisone was immediately initiated and the patient's condition rapidly improved. After a total in-hospital stay of 4 weeks, she recovered completely and could be discharged from hospital. Discussion : An Addison crisis requires rapid diagnosis and immediate treatment to end a life-threatening condition caused by critical glucocorticoid deficiency. In patients with non-specific symptoms, such as fatigue, hypotension, weight loss, and hyponatraemia, adrenocortical insufficiency should be considered as differential diagnosis. If patients suffer from an Addison crisis, clinical suspicion requires immediate substitution of hydrocortisone as this is essential for patient's survival. Venoarterial extracorporeal membrane oxygenation therapy can serve as a bridge to diagnosis and effective treatment in patients requiring temporary cardiopulmonary support, especially as salvage intervention for patients in cardiogenic shock. To our knowledge, this is the first case of a young patient with acute Addison crisis and cardiogenic shock, who was successfully salvaged by VA-ECMO support.